Arsenic content in red‐crowned crane (Grus japonensis) and invertebrates at the bottom of food chain in Zhalong wetland, northeastern China. Issue 5 (19th May 2015) - Luo, Jinming; Ye, Yajie; Gao, Zhongyan
Abstract: Arsenic (As) concentration was analyzed in four sediment‐inhabiting animals ( Pearsonia of Mollusca Gastropoda, Enchytraeus of Annelida Lumbricidae, Cybister japonicus Sharp of Hexapoda Dytiscidae and Chipangopaludina chinensis of Mollusca Gastropoda) from 19 sampling sites and eight carcasses of red‐crowned crane ( Grus japonensis ) to examine As transfer along the typical food chain in Wuyur catchments, northeastern China. Results indicated that As concentration in the prey of the red‐crowned cranes was elevated via the food chain. Geo‐accumulation indices at all sites were less than 0, which suggests that this region contained background As concentration. The four aquatic animal families containing As were land snail < water snail < beetle < earthworm. The highest As concentration was found in the liver of the red‐crowned cranes (145–441 ppb) followed by the kidneys (116–258 ppb) and muscles (36–94 ppb). The eggshells of red‐crowned cranes contained relatively high As concentration, which varied from 35 to 235 ppb, whereas the feathers had the lowest concentration, with an average of 25 ppb. The dietary exposure level to As of the red‐crowned crane population in Zhalong Wetland, Northeastern China was lower than the As toxicity threshold concentration. This study reported that eggshells are suitable indicators of As risk levels in red‐crowned crane.